Causes and Outcome of Neonatal Hyperbilirubinemia in Patiens Admitted in Bacha Khan Medical Complex/Gajju Khan Medical College Swabi - Muhammad Rizwan; Haji Gul; Hameed Ullah; Shah Jehan; Muhammad Zabih Ullah (Indus Journal of Bioscience Research, 2025)
Background: Neonatal hyperbilirubinemia is a common condition affecting a significant proportion of newborns, with potential for severe complications such as kernicterus if not identified and managed promptly. Despite advancements in neonatal care, the etiological spectrum and short-term outcomes of hyperbilirubinemia remain underexplored in many tertiary care hospitals in Pakistan. Objective: To determine the common causes and short-term outcomes of neonatal hyperbilirubinemia among neonates admitted to a tertiary care hospital. Methods: This descriptive cross-sectional study was conducted in the Department of Pediatrics, Bacha Khan Medical Complex, Swabi, over six months. A total of 276 neonates (≤28 days) admitted with hyperbilirubinemia were enrolled through consecutive sampling. Data on demographic, clinical, and etiological factors were collected and analyzed using descriptive statistics and chi-square tests. Results: The mean age at admission was 14.4 ± 7.9 days, mean gestational age 35.3 ± 4.5 weeks, and mean serum bilirubin 16.3 ± 5.2 mg/dL. ABO incompatibility was identified in 31.9% and Rh incompatibility in 35.1% of cases. Phototherapy was the main treatment (51.8%), while 25.4% required exchange transfusion. Overall, 64.9% of neonates were discharged after recovery, whereas 35.1% developed kernicterus. Hemolytic disease in siblings was the only factor significantly associated with kernicterus (p < 0.001). Conclusion: Kernicterus remains a major complication of neonatal hyperbilirubinemia in hospitalized infants. A positive family history of hemolytic disease strongly predicts adverse outcomes. Early recognition, effective phototherapy, timely exchange transfusion, and improved neonatal screening programs are essential to prevent kernicterus and reduce morbidity in resource-limited settings.